Origin, extent, and emplacement conditions of newly exposed pillow lavas and hyaloclastites in the Kverkfjöll region, Iceland - Iðunn Kara Valdimarsdóttir 1993- (2023)
A glaciovolcanic pillow and hyaloclastite formation chemically linked to the Kverkfjöll volcanic system (KVS) in the Icelandic highlands, erupted under a ~600 m thick glacier towards the end of the Upper Pleistocene (0.78-0.01 Ma) or in early Holocene (<0.01 Ma). This formation, situated in a glacial-river carved gully, consists of three pillow lava units, BB1, BB2, and BB3, and two tuff units, T1 and T2. The pillows are large compared to other studied Icelandic basaltic pillows that formed during a subglacial eruption. Their median diameters are 80, 86, and 91 cm for units BB1, BB2, and BB3, respectively, but many large pillows and structures (>4 m in diameter, megapillows) are found within the larger study area, often containing rosette-like jointing or shelf-like interiors. These may have acted as feeding pathways for other pillows. The tuff units show evidence of being deposited in a dynamic glacio-fluvial environment where changes in eruptive behavior and fluctuating water discharge played key roles. Chemical analysis via EPMA reveals that the pillows are of evolved compositions, relatively low in Mg and high in Fe and Ti and have a transitional alkalic character. Units BB1, BB2, and T1 were emplaced in quick succession. After some time, units BB3 and T2 were emplaced. This is supported namely by the sharp boundary of T1 and BB3, but BB3 also seems to have a more evolved composition than the other two pillow units. Bólstrabergs- og móbergsmyndun er ber einkennandi efnasamsetningu Kverkfjalla, gaus undir þrýstingi er svarar til um 600 m jökulþykktar. Aldur myndunarinnar er óræður en gera má ráð fyrir að eldgosið hafi átt sér stað í lok seinni hluta Pleistósen (0,78-0,01 Ma) eða byrjun Hólósen (<0,01 Ma). Myndunin sem um ræðir er að finna í gili rofnu af bræðsluvatni frá Dyngjujökli. Hún samanstendur af þremur bólstrabergseiningum, BB1, BB2 og BB3, og tveimur móbergseiningum, T1 og T2. Miðgildi þvermáls bólstra eru 80, 86 og 91 cm í einingum BB1, BB2 og BB3. Hinsvegar finnast stærri bólstrar (>4 ...